A Molecular Dynamics Investigation of Mycobacterium tuberculosis Prenyl Synthases: Conformational Flexibility and Implications for Computer‐aided Drug Discovery. (25th November 2014) - Kim, Meekyum Olivia; Feng, Xinxin; Feixas, Ferran; Zhu, Wei; Lindert, Steffen; Bogue, Shannon; Sinko, William; de Oliveira, César; Rao, Guodong; Oldfield, Eric; McCammon, James Andrew
<x xml:space="preserve">Abstract</x> With the rise in antibiotic resistance, there is interest in discovering new drugs active against new targets. Here, we investigate the dynamic structures of three isoprenoid synthases from Mycobacterium tuberculosis using molecular dynamics (MD) methods with a view to discovering new drug leads. Two of the enzymes, cis‐farnesyl diphosphate synthase (cis‐FPPS) and cis‐decaprenyl diphosphate synthase (cis‐DPPS), are involved in bacterial cell wall biosynthesis, while the third, tuberculosinyl adenosine synthase (Rv3378c), is involved in virulence factor formation. The MD results for these three enzymes were then compared with previous results on undecaprenyl diphosphate synthase (UPPS) by means of active site volume fluctuation and principal component analyses. In addition, an analysis of the binding of prenyl diphosphates to cis‐FPPS, cis‐DPPS, and UPPS utilizing the new MD results is reported. We also screened libraries of inhibitors against cis‐DPPS, finding ~1 μm inhibitors, and used the receiver operating characteristic–area under the curve (ROC‐AUC) method to test the predictive power of X‐ray and MD‐derived cis‐DPPS receptors. We found that one compound with potent M. tuberculosis cell growth inhibition activity was an IC50 ~0.5‐ to 20‐μm inhibitor (depending on substrate) of cis‐DPPS, a ~660‐nm inhibitor of Rv3378c as well as a 4.8‐μm inhibitor of cis‐FPPS, opening up the possibility of multitarget inhibition involving both cell wall biosynthesis and virulence factor formation.